Contemporary Educational Perspective: Howard Gardner And Daniel Goleman's Approach In Cultivating Adaptability And Resilience - Taryana Taryana; Muh. Safar; Bernardus Agus Rukiyanto; Mustofa Aji Prayitno (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Developing adaptability and resilience skills in students is a crucial aspect in preparing them to face the complex dynamics of life. This research explores the contemporary educational perspective with a focus on the approaches of Howard Gardner and Daniel Goleman in shaping students' adaptability and resilience. The literature study method is employed to analyze Gardner's views on Multiple Intelligences and Goleman's Emotional Intelligence concept within the educational context. The analysis highlights the synergies between these two theories in supporting the formation of students' adaptability and resilience in educational environments. The findings of this research are expected to provide practical insights to enhance educational strategies that support holistic development of students' adaptation and resilience across various educational settings. The research results indicate that the integration of both offers a strong foundation for a more comprehensive education, enabling educators to develop strategies that support holistic student growth, not only in academic realms but also in emotional and social aspects. Emphasizing the educator's role as a facilitator and role model in building student resilience, along with the appropriate use of assessments to measure and strengthen resilience, education can create a supportive environment for students to face life's challenges with the confidence and resilience needed.